Axial behaviors of recycled aggregate concrete cylinders under various confinement types: The experimental and theoretical analysis. (18th July 2022) - Rong, Chong; Qv, Yusong; Shi, Qingxuan; Wang, Peng; Li, Chenfei
Highlights: This paper presents the comprehensive study of the axial behaviors of three types of confined RAC. This paper focuses on the double-confinement mechanism of double-confined RAC. This paper proposes the constitutive models of the three types of confined RAC. Abstract: Recycled aggregate concrete (RAC) is favorable for environmental protection and sustainable development in building construction, and confinement can improve the mechanical properties of RAC. This paper presents the detailed experimental and theoretical studies on the axial behaviors of three types of confined RAC cylinders (i.e., steel-tube-confined RAC, glass-fiber-reinforced-plastic-confined RAC, double-confined RAC). Results show that the confined RAC cylinders have excellent mechanical behaviors, the load–displacement curve trend changes with the confinement type, and the proposed constitutive models can provide accurate prediction results.